1988
DOI: 10.1002/aic.690340210
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐programmed desorption: Multisite and subsurface diffusion models

Abstract: Two models are presented that can simulate two peaks in a temperature-programmed desorption (TPD) spectrum from a high surface area catalyst at atmospheric pressure: a multisite model and a subsurface diffusion model. The multisite model assumes that the two peaks arise from two distinct adsorption sites on the catalyst surface with different activation energies for desorption. The subsurface diffusion model assumes that the high-temperature peak is produced by adsorbate that diffuses into the subsurface regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 12 publications
3
43
0
1
Order By: Relevance
“…O 2 -induced elimination of metallic and alkaline activity is the result of the oxidation of these surface carbide sites, similar to the effects seen by Iglesia et al [11], and the lack of reversibility of this catalytic stifling is because of the extreme oxophilicity of the surface and thermodynamic favorability of O ⁄ binding as previously observed by Leary [5] and Liu [4]. In an independent experiment, H 2 O co-feed was also shown to diminish metallic activity of the carbide, but the oxidation was not as severe or complete as with the use of an O 2 co-feed.…”
Section: Proposed Ipa Dehydration Mechanism Over O ⁄ -Mo 2 Cmentioning
confidence: 58%
See 1 more Smart Citation
“…O 2 -induced elimination of metallic and alkaline activity is the result of the oxidation of these surface carbide sites, similar to the effects seen by Iglesia et al [11], and the lack of reversibility of this catalytic stifling is because of the extreme oxophilicity of the surface and thermodynamic favorability of O ⁄ binding as previously observed by Leary [5] and Liu [4]. In an independent experiment, H 2 O co-feed was also shown to diminish metallic activity of the carbide, but the oxidation was not as severe or complete as with the use of an O 2 co-feed.…”
Section: Proposed Ipa Dehydration Mechanism Over O ⁄ -Mo 2 Cmentioning
confidence: 58%
“…Leary and coworkers [5] experimentally demonstrated the role of surface O ⁄ on Mo 2 C as a poison for metal-catalyzed ethylene hydrogenation at 298 K. Leary and coworkers used online gas chromatographic and mass spectroscopic (GC and MS) analysis to observe the complication of bulk carbon removal concurrent with O ⁄ removal with temperature ramps under H 2 and He flow. PosadaPérez et al [6] used X-ray photoelectron spectroscopy (XPS) to monitor the O 1s region (528-533 eV) during sequential CO 2 dosing of the b-Mo 2 C surface at 300 K. Both O ⁄ and adsorbed CO were observed with the relative ratio of CO/O ⁄ increasing with CO 2 dosage, demonstrating the ability of O ⁄ on the Mo 2 C surface to inhibit cleavage of the second C@O bond and sequential hydrogenation reactions to CH 3 OH and CH 4 .…”
Section: Introductionmentioning
confidence: 98%
“…It was found that the residual oxygen in molybdenum carbide after passivation cannot be removed completely by hydrogen reduction unless the reduction temperature was increasing to 750 • C [42]. Besides, it was verified that desorption of CO or CO 2 at elevated temperature derived from the combination of carbidic carbon and dissolved oxygen during passivation [53]. For our catalysts prior to CO-TPD, the temperature of hydrogen pretreatment was 400 • C, far below 750 • C and thus the residual oxygen was not evitable.…”
Section: Temperature-programmed Desorption Of Co and Hmentioning
confidence: 95%
“…In the low temperature region, reduction peaks were not identical between samples. The major reduction peak at 198 °C was observed from the non‐promoted Mo 2 C sample and according to Leary et al any peak between 200–300 °C corresponded to oxygen removal from the Mo 2 C. Such a sharp “mobile oxygen” peak around 200 °C was not detected in the K 2 CO 3 promoted samples, indicating that the Mo 2 C surface may already have reacted with underlying potassium molecules.…”
Section: Resultsmentioning
confidence: 82%